Determinants of research engagement in academic obstetrics and gynaecology. Issue 1 (December 2016) - Fernandez, Ariadna; Sadownik, Leslie; Lisonkova, Sarka; Cundiff, Geoffrey; Joseph, K.
Abstract Background To identify the determinants of research engagement among faculty in an academic department of Obstetrics and Gynaecology. Methods All members of the Department of Obstetrics and Gynaecology at the University of British Columbia were mailed an online version of the Edmonton Research Orientation Survey (EROS) in 2011 and in 2014. High scores on overall research engagement and on each of the 4 subscales, namely, value of research, value of innovation, research involvement and research utilization/evidence-based practice were quantified. Analyses were carried out on both surveys combined and on the 2014 survey separately. Logistic regression was used to identify determinants of high levels of research engagement. Results The overall response rate was 37 % (130 responses; 54 respondents in 2011 and 76 respondents in 2014). The average EROS score was 140 (range 54 to 184) and 35 % of respondents had a score ≥150. Significant determinants of positive research engagement based on the overall EROS scale included being paid for research work (adjusted odds ratio [AOR] 22.1, 95 % confidence interval [CI] 2.47–197.7) and carrying out research during unpaid hours (AOR 6.41, 95 % CI 1.97–20.9). Age <50 years (AOR 11.0, 95 % CI 1.35–89.9) and clinical experience <20 years (AOR 19.7, 95 % CI 2.18–178.8) were positively associated, while journal reading during unpaid hours (AOR 0.21, 95 % CI 0.07–0.62) was negatively associated with specific EROS subscales. Conclusions In a setting with a positive research orientation, research engagement among the faculty was associated with paid research time, research work and journal reading during unpaid hours and more recent entry into clinical practice.